Dying can be complicated - Abd Razak, Dzulkifli (2005)
WE all acknowledge that life can be full of ironies. Indeed, some would say that is what makes the world go round. As though that is not enough, in the last one week alone, we also learn that death, too, can be part of that irony. There are at least two cases in point to illustrate this. First, it was the death of Pope John Paul II at the age of 84 on April 2 after a long and amazingly vigorous battle with his body's in firmities. What began as a simple urinary tract infection later triggered a cascade of medical problems. Ultimately, it left the Polishborn Pope clinging to life from a seeming innocuous infection — which in most cases would be easily re versible. Unfortunately for the Pope, who was named Karol Jozef Wojtyla at birth, it turned lifethreatening, given that he was elderly and was also suffering from Parkinson's disease, a brain disorder characterised by the impairment or degeneration of certain brain nerve cells.